Peripheral Inflammatory Parameters in Patients with Antisocial Personality Disorder - Tasci, Gulay; Kaya, Suheda; Korkmaz, Sevda; Atmaca, Murad (Turkish Neuropsychiatry Assoc-Turk Noropsikiyatri Dernegi, 2022)
Introduction: The aim of the study was to examine the peripheral inflammatory parameters in patients with Antisocial Personality Disorder (APD) including white blood cell levels, red cell distribution width (RDW), mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), basophil-to-lymphocyte ratio (BLR) by comparing with those of healthy controls. Methods: 48 patients diagnosed with APD and a matched healthy control group of 52 individuals were included in our study. Venous blood samples were taken from the participants in the fasting state and at approximately the same time of the day. Socio-demographic data sheet, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Barratt Impulsiveness Scale (BIS-11), Buss-Durkee Hostility Inventory (BDHI) were applied to all of the participants. Results: RDW and basophil cell levels were found significantly higher in the patients than the controls (p=0.005, p=0.038 respectively). BLR was found significantly higher in the participants with alcohol use than those without alcohol use (p=0.016). No significant difference in other laboratory parameters was found between the patient group and the control group. Scores of BDI, BAI, BIS-11, motor impulsivity subscale and physical aggression, anger, hostility and verbal aggression subscales of BDHI, and the total score of BDHI were significantly higher in patients than controls (p<0.001, p<0.001, p<0.001, p<0.001, p<0.001, p=0.003, p=0.001, p<0.001 respectively). A positive correlation was determined between the scale scores and the ROW, basophil, monocyte, lymphocyte levels among the laboratory parameters, and a negative correlation was determined between the MPV levels and the depression and impulsivity levels. Conclusion: The results of our study suggested that inflammation might play a role in the etiopathogenesis of APD. Furthermore, a significant relationship was found between the severity of symptoms and some inflammatory parameter levels such as RDW and basophil in patients with APD.
Keywords: Antisocial Personality Disorder; inflammatory markers; basophil; RDW